Evaluación del barbasco (Lonchocarpus nicou) al 10%, 15% y 20% como antipulgas en perros domésticos en la Clínica Veterinaria Animal Vet’s en la ciudad del Puyo - Yugcha Quispe, Lady Nataly (2015)
The Barbasco or cube (Lonchocarpus nicou) known in the Amazon in South America, belongs to the family of leguminous, being highly appreciated by the high content of rotenone, a toxic substance that is obtained from the roots. Traditionally, the milky bruised roots of mullein, are used by the natives for artisanal fishing, and for certain cures. This research was conducted at the Animal Veterinary Clinic Vet`s, located between the streets July 20 and Chimborazo in the working class suburb of the city of Puyo, Pastaza Province. The objective of the research was to evaluate the solution of mullein (Lonchocarpus nicou) 10%, 15% and 20% in domestic dog’s flea. The methodology used was experimental and that 40 dogs, which were divided into four groups of 10 experimental units were used for each treatment….